Investigating the conservation value of leopard population indices obtained through camera traps in the greater Kruger region of South Africa - Smyth, Lucy (Department of Biological Sciences, 2023)
Leopards (Panthera pardus) are one of the most widespread large felids, historically ranging across much of Africa, the middle east and Asia. Their solitary and elusive nature has allowed them to persist in many areas where other members of the large carnivore guild have been extirpated. However, the combined effects of habitat loss, reduced prey abundance, unsustainable trophy hunting, negative interactions with humans and a growing demand for body parts are taking their toll on the species. Leopards now occupy between 25 and 37% of their historic range, and population densities are decreasing across many small reserves in South Africa. Modifications to current management regimes, informed by monitoring programs, are thus crucial to the persistence of the species. Kruger National Park (KNP) is the largest protected area in South Africa and has thus been assumed to be an inviolate refuge for leopards, despite a lack of data on key leopard population parameters. In this thesisI provide crucial density estimates for leopardsin different regions of KNP and adjacent privately managed areas. Additionally, I explore other often neglected data routinely recorded by camera traps that are potentially important to refining population monitoring efforts. Specifically, I investigate temporal leopard activity quantified using time stamps on photographs of individuals and the potential drivers of activity patterns across differentsites as well asthe relationship between phenotypic similarity derived from photographs of known individuals and relatedness estimates from pedigree data. Multisession spatial capture-recapture (SCR) models proved useful in estimating density across sites and looking at drivers of density. Leopard density ranged from 2.6 ± 0.6 to 13.2 ± 2.6 leopards/100km2 across the sites surveyed. Differences in reserve management appear to be having a substantial effect on the density of leopard populations, providing cause for concern that leopards are being negatively affected by anthropogenically driven mortalities and populations are thus failing to reach their carrying capacity. Normalised Difference Vegetation Index (NDVI) was also an important driver of density, showing a strong interaction with Reserve Type. Higher NDVI was more strongly positively correlated with leopard density in better protected reserves. Leopard activity was predominantly nocturnal with crepuscular peaks and diel activity patterns that differed between sites. These differences were driven mainly by seasonal variation in temperatures and not the relative abundance of humans, potential competitors, or prey. Leopard activity also varied on a lunar scale, with leopards showing higher activity levels with greater lunar illumination, possibly in response to decreased hunting success at higher light levels. I quantified phenotypic similarity in leopards from the Sabi Sand Game Reserve (SSGR) by measuring the resemblance of flank rosette patterns using Hotspotter and ImageJ software and manually recording the resemblance of whisker spot markings. I then compared these metrics to relatedness scores obtained from a pedigree derived from known maternal relationships with offspring. Despite six of 15 phenotypic metrics showing significant heritability, this relationship was noisy at the population level and thus phenotypic resemblance measures derived from photographic data could not provide information on the level of relatedness between leopard individuals from within populations. The data collected throughout this study provides a comprehensive baseline of leopard population status in KNP and select adjacent and contiguous private protected areas. Density remains highest in the SSGR which invests heavily in preventing negative anthropogenic impacts, is intermediate in KNP where there is concern over the potential for some human induced mortality and is lowest in Karingani Game Reserve (KGR), a protected area in its infancy where the effects of protection have not yet had time to materialise. This study also provides an indication of the uses and limitations of camera trap data, and how it can be helpful in informing leopard conservation and management.